Historical and conceptual foundations of measurement in the human sciences : credos and controversies - Briggs, Derek C. (New York, NY : Routledge, 2022)
"Historical and Conceptual Foundations of Measurement in the Human Sciences explores the assessment and measurement of non-physical attributes that define human beings: abilities, personalities, attitudes, dispositions, and values. The proposition that human attributes are measurable remains controversial, as do the ideas and innovations of the six historical figures-Gustav Fechner, Francis Galton, Alfred Binet, Charles Spearman, Louis Thurstone and S. S. Stevens-at the heart of this book. Across ten rich, elaborative chapters, readers are introduced to the origins of educational and psychological scaling, mental testing, classical test theory, factor analysis, and diagnostic classification; and to controversies spanning the quantity objection, the role of measurement in promoting eugenics, theories of intelligence, the measurement of attitudes, and beyond. Graduate students, researchers, and professionals in educational measurement and psychometrics will emerge with a deeper appreciation for both the challenges and the affordances of measurement in quantitative research. Derek C. Briggs is Professor in the Research and Evaluation Methodology Program in the School of Education and Director of the Center for Assessment Design Research and Evaluation at the University of Colorado Boulder, USA. A former editor of the journal Educational Measurement: Issues & Practice, he is the 2021-22 President of the National Council on Measurement in Education"--
Keywords: Psychometrics -- History; Psychological tests -- History; Educational tests and measurements -- History; Scaling (Social sciences) -- History; EDUCATION / Testing & Measurement; EDUCATION / Educational Psychology